Implementasi Kebijakan Pencegahan dan Penurunan Stunting di Kabupaten Kupang - Fernandez, Dominikus; Long, Belandina L.; Rene, Mariyani Oktafiana (Universitas 17 Agustus 1945 Surabaya, 2023)
Stunting is a public problem whose solutions use various approaches, policies, models, or specific analyses. This paper analyzes policy with a policy context approach such as Griendle's concept. The choice of this analysis is based on the consideration that the policy context aspect is always a determinant of policy performance. Power, interests, and strategies of the actors involved; institution and regime characteristics; compliance; and responsiveness. This research used qualitative methods, and the results were analyzed descriptively. The research location was in Kupang Regency, with overall observations including the center, the periphery, and the target groups. Data collection was organized using structured interviews, observation, and document study. The results show varied implementation performance between the observed areas due to the policy context, even though stunting prevention and reduction policies are based on and supported by the same policies and street-level implementation. It can be concluded that the policy context always determines implementation performance, and it is recommended that implementors always be more intensive and active in paying attention to variations in the policy environment.